Harmonization of family law in Serbia with the law of the EU - Panov, Slobodan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The author analyzes the different models of harmonization, and states that modern ideas of the owners have the final time different from the advertised nobility. Family law, because the spiritual specifics, a special issue of harmonization. Author harmonization of the different family law (need harmonization with the Constitution of Serbia, the harmonization of the term, harmonization of the Family Act of Serbia ...) and the harmonization of family law with EU law (the author talks about harmonization useful, but the EU law as inaccurate and unnecessary model).